Deformation Criterion for Determining the Distance Between Normal Cracks in Reinforced Concrete Beams under Plane Bending - D. A. Pekin (Железобетонные конструкции)
A brief review of the development of a new section of solids mechanics — mechanics of reinforced concrete — is given. For rod reinforced concrete elements, the expediency of allocating a new subsection – mechanics of rod reinforced concrete elements with normal cracks — is substantiated. Classical prerequisites and assumptions for determining the distance between normal cracks in the state of pure bending are considered in detail, and the need for their complete revision based on the ultimate tensile strength of concrete and the development of a deformation criterion is substantiated.